Integrated Economic Value Added: Intellectual Capital Estimation Issue - ИсакинМаксим Александрович; ОсколковаМарина Александровна; ШакинаЕлена Анатольевна (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2011)
Defining the strategic vision of the company, managers and owners almost always have a shortage of information about different investments potential effectiveness. At the first step the company should find a compromise between investments in traditional assets and intellectual capital accumulation. RAVE concept is mainly based on the premise that the intellectual capital outcomes, including its knowledge, the company marketing policy, purchasing and staff development, exceed the traditional assets outcomes. This article represents the critical analysis of the approach designed by BCG consultants and is devoted to the integrated economic value added - method development.